Willingness to Pay Analysis of Sekar Arum Organic Rice Products (Case Study of Gapoktan Damarwulan Ungkal Jaya: Kediri Regency) - Putra, Demmy Filsafa Ratna (PT FORMOSA CENDEKIA GLOBAL, 2024)
The growing trend of healthy lifestyles around the world is driving an increase in demand for organic products, including rice, which is one of the staple foods. In Indonesia, the majority of farmers still grow rice conventionally, producing non-organic rice. However, the increase in organic rice farming land in Madiun City has not been matched by an effective marketing system or special pricing rules. This study uses a quantitative approach with the contingent valuation method and logistic regression analysis to measure consumers' willingness to pay more for organic rice. The results show that 93% of respondents are willing to pay more, with an average willingness to pay of IDR 23,310, an increase of 16.55% from the initial price. The most influential variable is access to organic rice.